Political migration discourses on social media: a comparative perspective on visibility and sentiment across political Facebook accounts in Europe. Issue 7 (18th May 2020) - Heidenreich, Tobias; Eberl, Jakob-Moritz; Lind, Fabienne; Boomgaarden, Hajo
ABSTRACT: Migration has been dominating media and political discourses in Europe in recent years. Previous studies have mainly mapped migration discourses in traditional media or conventional channels of party communication, often in a single country. Migration-related party communication on social network sites has been largely neglected. This study analyses migration discourses in the Facebook accounts of political actors ( n  = 1702) across six European countries (Spain, UK, Germany, Austria, Sweden and Poland). On the basis of automated content analyses, we present new insights into the visibility of migration as a topic and sentiment about migration, revealing country- and party-specific patterns. Migration is a more prominent topic in countries with positive net migration ('receiving countries') than in countries where net migration is neutral or negative. Although we did not find support for the assumption that right-leaning parties talk more, and more negatively, about migration, our results do suggest a distinct pattern that applies to parties of both the extreme left and the extreme right. Political actors from parties of the extreme left and the extreme right of the political spectrum address migration more frequently and more negatively than more moderate political players.